Sociological Analysis of the Commercial Hunting on the Lands of Small-Numbered Indigenous Peoples of the North in the Arctic Zone of the Sakha Republic Republic (Yakutia) - V. Velichenko, Valery; N. Sleptsov, Anatoly (International Journal of Criminology and Sociology, 2022)
The article presents the results of the analysis of commercial hunting of the most typical communities of small indigenous peoples of the North of Russia living in the Arctic zone of Yakutia, for which hunting largely determines the life quality. For the analysis, statistical data and internal hunting materials were used with the participation of the article authors. In preparing this article, we used statistical data and materials from the Yakutia Department of Hunting Management, as well as stock materials from the Institute. We used statistical methods to process the materials. For the first time, the materials of the intra-economic hunting arrangement conducted in the areas assigned to small peoples are analyzed. For the first time, the article provides data on the history of establishing hunting grounds in Yakutia as part of all-Russian activities. The article provides the results of foreign researchers' studies dedicated to the issue of framing and maintaining the traditional lifestyle of indigenous peoples of the North. Based on the analysis of the structure of commercial production, it is demonstrated that hunting trends are adapted to the extreme weather and climatic conditions of the Arctic and defined by the wildlife species that inhabit these regions. Backed by retrospective analyses, considerable changes in the structure of commercial production are illustrated. These are linked to the decrease in numbers of one of the populations of wild reindeer and the decreasing demand for natural fur, factors that have reduced the importance of traditional hunting in the lives of the region’s ethnic groups. It is revealed that the forecast of large-scale development of mineral resources in the Arctic regions of Yakutia demands that preventive measures be taken to protect natural resources that are the foundation for the traditional crafts of the indigenous peoples of the North.